Kegagalan Negara dalam Good Governance Pengembangan One Village One Product Pada Masyarakat Desa di Kabupaten Sambas - Rusdiono, Rusdiono; Sudagung, Adityo Darmawan; teyseran, silverius (Institut Pemerintahan Dalam Negeri, 2025)
This study analyses the state's failure to implement good governance in the One Village One Product (OVOP) programme in rural communities of sambas Regency. It focuses on three main factors: abuse of power and ethical violations, lack of transparency and accountability, and limited community participation. Using a descriptive qualitative method, the study analysed interviews with local officials, village officials, and communities, as well as official documents related to OVOP implementation. The results showed that the government's dominance in programme development hindered community and private sector involvement. The practice of nepotism, budget non-transparency, and decision-making that is not based on local needs causes the OVOP programme to be short-term project-oriented without clear sustainability. The conclusion of this study confirms that the failure of good governance implementation in OVOP is caused by weak control, lack of collaboration between actors, and low accountability. Governance reforms emphasising transparency, inclusive participation, and accountability are needed to improve the effectiveness of community-based development programmes. Keywords: State Failure; Good Governance; One Village One Product; Transparency, Community Participation; Accountability